2021
DOI: 10.1080/1550428x.2021.1935381
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Attitudes toward Lesbian and Gay Parenting in an Ecuadorian Sample

Abstract: In the past few years, Ecuador has experienced legal changes toward the recognition of sexual minority rights. However, lesbian and gay (LG) individuals and couples still face legal obstacles to become parents and social barriers that place their families in disadvantage compared to their heterosexual counterparts. To date, it is not known whether the legal changes reflect society's move toward a more progressive and accepting climate. This study analyzed the attitudes toward LG parenting in an Ecuadorian onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Results from our study also indicate that people view sexual orientation as a trait that is socially learned by observation and that children in same-sex families would have higher chances to be gay and lesbian themselves (Rye & Meaney, 2010). The ideas about the etiology of sexual orientation have been found to be one of the most important predictors of attitudes toward same-sex parenting (Costa & Salinas-Quiroz, 2019;Frias-Navarro et al, 2015;Hermosa-Bosano et al, 2021a). However, behind these ideas there are several prejudiced notions that need to be critically questioned such as the fact that children discovering themselves as gay is wrong or undesirable (Kuvalanka, 2013).…”
Section: Discussionsupporting
confidence: 60%
“…Results from our study also indicate that people view sexual orientation as a trait that is socially learned by observation and that children in same-sex families would have higher chances to be gay and lesbian themselves (Rye & Meaney, 2010). The ideas about the etiology of sexual orientation have been found to be one of the most important predictors of attitudes toward same-sex parenting (Costa & Salinas-Quiroz, 2019;Frias-Navarro et al, 2015;Hermosa-Bosano et al, 2021a). However, behind these ideas there are several prejudiced notions that need to be critically questioned such as the fact that children discovering themselves as gay is wrong or undesirable (Kuvalanka, 2013).…”
Section: Discussionsupporting
confidence: 60%
“…Ecuadorian men, heterosexual, those who practice their religion, those who attend more frequently to religious services, and those who identify as conservative showed higher levels of prejudice against lesbian and gay individuals as well as less support toward their rights, namely same-sex marriage and parenting 33 . Furthermore, in the same South American country, it was found that older participants, those who were married and those with children had less favorable attitudes toward same-sex parenting 34 . Costa and Salinas-Quiroz 14 established that Mexican men, and religious participants showed higher levels of negative beliefs about same-sex parenting.…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, there is some evidence that changes in sexual prejudice arise from advancements in legal rights for sexual minorities 28 . The present study is the first to examine attitudes toward same-sex parenting among several CAHN, after previous research focused mostly on individual countries in the region such as Chile, Colombia, Ecuador or Mexico 14 , 30 34 .…”
Section: Introductionmentioning
confidence: 99%